Armazenamento a frio e aplicação de reguladores vegetais no enraizamento de estacas radiculares e caulinares de framboeseira - Tiberti,Andrei Spaziani (2015)
The objective of this research was to verify the potential rhizogenic stem cuttings and root of raspberry (Rubus idaeusL.). Cuttings of 'Batum' cultivar was stored cold (4°C) for 10, 20 and 30 days, and a control without storage. Subsequently, the cuttings were treated with indolebutyric acid (IBA) at 0, 1000, 2000, 3000 and 4000mg L-1 and root cuttings with benzylaminopurine (BAP) at 0, 300, 600, 900, 1200 and 1500mg L-1 by 10 seconds. The cuttings were buried in 2/3 of its length in the vertical position, and root was completely buried in the horizontal position at three inches deep. It was used vermiculite medium as substrate, and these experiments were conducted in a greenhouse with 50% shading. Evaluations were made ​​75 days after planting the cuttings. It was concluded that the use of cuttings is not feasible and that the root cuttings need not be stimulated by cold storage or treatment with BAP.